Eco-Friendly Ultrasound-Assisted Synthesis of Silver Nanoparticles Mediated by Tea Leaf Extracts and Their Potential Applications - Muliawati, Nindya Tri; Fajar, Malik; Sholeha, Novia Amalia; Ramdhan, Mohamad Alief; Laila, Farida; Sujarnoko, Tekad Urip Pambudi; Yulianti, Wina; Supardan, Atep Dian; Listiasari, Faranita Ratih; Resmeiliana, Ika (Universitas Pendidikan Mandalika, 2025)
The green synthesis of silver nanoparticles (AgNP) presents notable benefits, such as environmental sustainability, simplicity, cost-effectiveness, and scalability for industrial applications. This study utilized green tea leaves (Camellia sinensis), which are abundant in catechins and polyphenols, as natural reducing and stabilizing agents. Ultrasonic-assisted synthesis was utilized to improve extraction and reduction processes, as acoustic cavitation induced by ultrasonic waves facilitates efficient mass transfer, accelerates nucleation, and enhances nanoparticle dispersion. This method provides an environmentally sustainable and economically viable alternative to conventional AgNP synthesis, enhancing the sustainability of nanoparticle production. The successful synthesis of AgNP was evidenced by the distinct color change of the tea extract from green to brown, accompanied by the formation of a brown colloidal suspension, in accordance with the Surface Plasmon Resonance (SPR) phenomenon. The UV-Vis spectrophotometric analysis confirmed AgNP formation, evidenced by a characteristic absorption peak at approximately 430 nm. The synthesized AgNPs were utilized as a colorimetric sensor for Fe³⁺ ions in aqueous solutions, demonstrating distinct color changes and SPR band shifts upon interaction with the metal. This illustrates their capability as environmentally friendly nanomaterials for the swift and precise detection of heavy metals, aiding in sustainable environmental monitoring. This research integrates ultrasonic-assisted synthesis with green tea extract, presenting a viable approach for the large-scale, environmentally sustainable production of nanoparticles.